Gamified Vocabulary Learning: EFL Students’ Perceptions of Using Duolingo to Enhance English Vocabulary Mastery - Alim, Sabarin; Aisyah, Siti; Sabat, Yulianto; Hastuti, Umi Nur; Andayani, Endah Alamsari (Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates EFL students' perceptions of using Duolingo, a gamified mobile application, to enhance English vocabulary mastery. Recognizing vocabulary as a foundational element for effective English communication and acknowledging the limitations of traditional learning methods, this research explores the efficacy of digital, gamified approaches. Adopting a qualitative descriptive research design, data were collected from 20 second-semester English Education Department students at Universitas PGRI Delta Sidoarjo (UNIPDA) through observations, semi-structured interviews, and Likert scale questionnaires. Findings indicate that Duolingo significantly enhances student motivation and engagement due to its gamified features (XP, levels, streaks) and user-friendly, flexible interface. Students reported notable improvements in passive vocabulary knowledge, particularly in word recognition and comprehension, facilitated by the app's repetitive, visual, and audio-text integration. However, a key limitation identified is Duolingo's constrained effectiveness in fostering active vocabulary use and productive language skills, as it offers limited opportunities for real-life conversational application. The study concludes that Duolingo is a highly effective supplementary tool for building receptive vocabulary but should be integrated with interactive communicative methods to achieve comprehensive language proficiency. Future research could quantitatively compare Duolingo's impact on receptive versus productive vocabulary, explore optimal integration strategies into EFL curricula, and investigate long-term retention rates.